Uncertain Business : Risk, Insurance, and the Limits of Knowledge - Ericson, Richard V., 1948-2007 (Book collections on Project MUSE., 2004)
We live in an age of increasing doubt about whether our institutions and technologies can provide security against risks, many of which they themselves have created. Uncertain Business is an unprecedented inquiry into insurance industry practices and what they tell us about risks and uncertainties in contemporary society. The core of the book is ethnographic studies in distinct fields of insurance: premature death, disability, earthquake, and terrorism. These studies reveal that uncertainty pervades different fields of insurance, the very industry that is charged with transforming uncertainty into manageable risk. Scientific data on risk are variously absent, inadequate, controversial, contradictory, and ignored. Insurers impose meaning on uncertainty through non-scientific forms of knowledge that are intuitive, emotional, aesthetic, moral, and speculative. Nevertheless, the nature of uncertainty and the response to it varies substantially across the fields studied, showing how contemporary society is characterized by competing risk logics. Insurers' perceptions and decisions about uncertainty with potential for windfall profits as well as catastrophic losses create crises in insurance availability and provoke new forms of inequality and exclusion. Hence, while the insurance industry is a central bulwark against uncertainty, insurers also play a key role in fostering it.